A Combination of Google Translate and Grammarly App for a Better Translation Quality of Academic Papers - Hartono, Rudi; Subhan, Subhan; Hetami, Fatma; Anjaniputra, Agung Ginanjar (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
This research was based on concerns about the quality betterment of the academic paper translations translated from Indonesian to English. The quality of the academic paper translation is still inaccurate and less natural because the authors translated using Google Translation. The combination of Google Translate and Grammarly Application (GTG-com App) as a developed translation application can be one application of translation that gives an effective and fast solution in translating academic papers from Indonesian into English. This app can improve the quality of translation grammatically, syntactically, lexically, and mechanically. The goal of this study is to help translators translate Indonesian academic papers into more accurate and natural English. The research method used is Research and Development (R & D). In this study, first, the researchers did a translation pretest of translating five academic papers done by five lecturers as the participants used Google Translate (GT) from Indonesian into English. Second, we assessed the translation products based on the accuracy and naturalness levels using the translation quality assessment scales. Third, we distributed questionnaire 1 of translators’ responses on GT translation products to five lecturers as the respondents and interviewed them about their needs for a new trans tool that can help them easily, accurately, naturally, and quickly translate their academic papers. Fourth, we developed GTG-Com App. Fifth, we did a translation posttest using GTG-Com App. Sixth, we compared the translation scores of GT translation to the GTG-Com App translation products. Seventh, we distributed questionnaire 2 of translators’ responses on GTG-Com App usage, and Eighth, we interviewed the same respondents about the GTG-Com App effectiveness. The data were analyzed descriptively using the t-Test formula and translation quality assessment scales. The research results show that GTG-Com App produced more accurate and natural translations than Google Translate (GT) did. The translation accuracy of using the GTG-Com App is 2.65 (accurate) while using GT is just 2.00 (less accurate). In this case, there is a difference in the score of 0.65 and the GTG-Com App is more accurate. The translation naturalness of using the GTG-Com App is 2.74 (natural) while using GT is just 2.48 (less natural). Similarly, at the level of naturalness GTC-com App produces a more natural 0.26 than GT.